Bioprospecting Keratinous Materials - Jones, LN (Medknow Publications, 2010)
The concept of bioprospecting for bioactive peptides from keratin-containing materials such as wool, hair, skin and feathers presents an exciting opportunity for discovery of novel functional food ingredients and nutraceuticals, while value-adding to cheap and plentiful natural sources. The published literature reports multiple examples of proline-rich peptides with productive bio-activity in models of human disease including tumour formation, hypertension control and Alzheimer’s disease. Bioactive peptides have been identified from food and other protein sources however the bioactivity of keratin-related proteins and peptides is largely unknown. Considering the high representation of proline-rich peptides among proven bioactive peptides, the proline-rich character of keratinous proteins supports current research. A selection of mammalian (cow epidermis, sheep wool) and avian (chicken feather) keratinous materials were subjected to enzymatic hydrolysis using established processing methods. A bio-assay of determining inhibition of early stage amyloid aggregation involved using a model fibril-forming protein – reduced and carboxymethylated bovine K-casein (RCMk-CN) and quantitation of fibril development with the amyloid-specific fluorophore, Thioflavin T (ThT). The assay was fully validated for analytical repeatability and used together with appropriate positive controls. Peptide library products derived from chicken feather (n=9), sheep wool (n=9) and bovine epidermis (n=9) were screened in the fibril inhibition assay based on K-casein. 3 of 27 products exhibited interesting levels of bio-activity with regard to fibril inhibition. HPLC profiles provide an indication of the complexity of the assemblage of peptides in the three active products. We conclude the bioprospecting research using keratinous materials shows promise for discovery of useful bioactive peptides.